Psychological Distress, Social Support, Coping Style, and Perceived Stress Among Medical Staff and Medical Students in the Early Stages of the COVID-19 Epidemic in China - Li, Zhe; Yi, Xin; Zhong, Mengting; Li, Zhixiong; Xiang, Weiyi; Wu, Shuang; Xiong, Zhenzhen (Frontiers in Psychiatry, 2021)
Background: The COVID-19 pandemic has had impact that may contribute to a rise in mental health problems. The present study was aimed to better understand psychological status among medical staff and medical students during the early epidemic and to explore the influence factors of psychological distress. Methods: A cross-sectional survey was conducted online from February 2-14, 2020. We collected general information related to the COVID-19 outbreak. Respondents were assessed using the Kessler-6 Psychological Distress Scale (K6), Social Support Rating Scale (SSRS), Perceived Stress Scale (PSS) and Simplified Coping Style Questionnaire (SCSQ). Stepwise multiple linear regression was performed to identify factors influencing psychological distress. Results: 528 respondents returned valid questionnaires. Medical staff and Medical students scored averages of 6.77±5.04,15.48±8.66 on the K6, 37.22±11.39, 22.62±11.25 on the SSRS and 18.52±7.54, 28.49±11.17 on the PSS respectively. Most medical staff (279, 91.77%) and 148 medical students (66.07%) showed a positive coping style. Social support, perceived stress, hours spent watching epidemic-related information per day and frequency of epidemic-related dreams were identified as factors influencing psychological distress among medical staff and medical students. Coping style emerged as a determinant of psychological distress among medical staff. Conclusions: In the early stages of the COVID-19 epidemic in China, medical staff and medical students were at moderate to high risk of psychological distress. Our results suggest that psychological interventions designed to strengthen social support, reduce perceived stress and adopt a positive coping style may be effective at improving the mental health of medical staff and medical students.